Construction Cost Analysis of Spun Pile and Bored Pile Foundations for Aqueduct C of the Raw Water Supply Supplemental Project in Aceh Province - Ghufran Helmi Aziz; Andi Patriadi; Esti Wulandari (Publica Scientific Solution, 2026)
Selecting the optimal deep foundation system is a critical task in major infrastructure projects, requiring a balance between structural performance, geotechnical constraints, and economic viability, as foundation costs typically represent a significant portion of the total budget. Bored piles and spun piles are two widely adopted deep foundation types, each offering distinct advantages in terms of capacity, installation speed, and environmental impact. Given the necessity for cost optimization in the Raw Water Supply Supplemental Project in Aceh Province, this study focuses on comparing the construction costs of these two foundation types for Aqueduct C. The foundation plan for Aqueduct C requires a total pile length of 2,870 meters with a diameter of 60 cm. The analysis uses unit cost data based on the Ministerial Regulation's Unit Price Analysis (AHSP) tables. The calculation results show that the total cost for the bored pile foundation is Rp2,847,074,353.90, while the total cost for the spun pile foundation is Rp3,205,844,730.90. This indicates that the bored pile foundation is more cost-effective for this specific project by approximately Rp358,770,377.00. The structural capacity analysis confirmed that the designed foundation group safely supports the axial load transferred by the piers.